Biodegradable film as well as preparation method and application thereof

By using the mechanical support layer composed of PPC and PBAT and the self-adhesive layer of PPC diol in the biodegradable film, the problem of insufficient self-adhesiveness of the biodegradable wound film is solved, and a biodegradable film with high viscosity and uniform thickness is achieved, with good mechanical properties and wide application prospects.

CN119552585APending Publication Date: 2025-03-04CHANGCHUN INSTITUTE OF APPLIED CHEMISTRY CHINESE ACADEMY OF SCIENCES
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411867581.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The existing biodegradable wrapping films lack self-adhesion, and traditional additives such as polyisobutene are not biodegradable, resulting in processing difficulties and uneven product products.

Method used

A mechanical support layer consisting of polypropylene carbonate (PPC) and polyadipate/butylene terephthalate (PBAT) was used, and combined with polypropylene carbonate (PPC diol) as the self-adhesive layer, a biodegradable film with high viscosity and uniform thickness was prepared by casting and coating.

Benefits of technology

It has achieved high self-adhesion and thickness uniformity of biodegradable films, and has high horizontal and vertical tension breaking force. It is suitable for agriculture, garbage collection and treatment, food packaging and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a biodegradable film as well as a preparation method and application thereof, and belongs to the technical field of materials. The biodegradable film comprises a mechanical supporting layer and a self-adhesive layer which are connected in sequence, the mechanical supporting layer is prepared from the following components in parts by weight: 5 to 80 parts of polypropylene carbonate; 18.5 to 94.5 parts of PBAT (Polybutylene Terephthalate); 0.5 to 1.5 parts of a compatilizer; the self-adhesive layer is made of poly (propylene carbonate) glycol; and the thickness of the biodegradable film is 10 to 50 [mu] m. The biodegradable film is uniform in thickness and high in viscosity, has relatively high transverse and longitudinal tensile strength, and can better meet daily requirements.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of material technology, and in particular to a biodegradable film and a preparation method and application thereof. Background Art

[0002] Biodegradable materials have received great attention and attention. my country's biodegradable materials entered a period of rapid development in 2020, with the establishment of a large number of production lines for biodegradable materials such as polybutylene adipate / terephthalate (PBAT), polylactic acid (PLA), and carbon dioxide-propylene oxide copolymer (PPC).

[0003] Biodegradable plastic film technology is gradually maturing, with commercially available products such as biodegradable mulch films, tote bags, garbage bags, and courier bags. However, biodegradable stretch film still suffers from performance deficiencies, primarily due to insufficient self-adhesion, making it difficult to seal after wrapping. Traditional stretch film typically enhances self-adhesion by adding polyisobutylene, but polyisobutylene is not biodegradable and is incompatible with biodegradable materials, limiting its application. Existing technologies often use inherently adhesive materials such as rosin to enhance the self-adhesion of biodegradable stretch film. However, when these materials are directly melt-blended with biodegradable materials, insufficient addition leads to insufficient precipitation and insufficient self-adhesion. Excessive additions can cause these adhesive small molecules to adhere to processing equipment, complicating processing. Furthermore, their high viscosity makes them difficult to mix evenly with other materials. Furthermore, their poor melt strength can lead to uneven film production during melt processing, whether in blown film or cast film production.

[0004] Therefore, it is of great significance to research and develop a new type of biodegradable film with good self-adhesion and uniform thickness. Summary of the Invention

[0005] In view of this, the technical problem to be solved by the present invention is to provide a biodegradable film and its preparation method and application. The biodegradable film has uniform thickness, high viscosity, and high transverse and longitudinal tensile strength.

[0006] In order to achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0007] The present invention provides a biodegradable film comprising a mechanical support layer and a self-adhesive layer connected in sequence;

[0008] The mechanical support layer comprises the following components in parts by weight:

[0009] Polypropylene carbonate (PPC): 5-80 parts;

[0010] Polybutylene adipate / terephthalate (PBAT): 18.5-94.5 parts;

[0011] Compatibilizer: 0.5-1.5 parts;

[0012] The self-adhesive layer is polypropylene carbonate diol (PPC diol);

[0013] The thickness of the biodegradable film is 10-50 μm; in some specific embodiments of the present invention, it is preferably 20 μm or 50 μm.

[0014] More preferably, the mechanical support layer comprises the following components in parts by weight:

[0015] Polypropylene carbonate (PPC): 5 parts;

[0016] Polybutylene adipate / terephthalate (PBAT): 94.5 parts;

[0017] Compatibilizer: 0.5 parts.

[0018] Or, more preferably, the mechanical support layer comprises the following components in parts by weight:

[0019] Polypropylene carbonate (PPC): 80 parts;

[0020] Polybutylene adipate / terephthalate (PBAT): 18.5 parts;

[0021] Compatibilizer: 1.5 parts.

[0022] Preferably, the compatibilizer is selected from a terpolymer of carbon dioxide, propylene oxide and a functional monomer, wherein the functional monomer is selected from allyl glycidyl ether or glycidyl methacrylate.

[0023] Preferably, the number average molecular weight of the polypropylene carbonate (PPC) is 100-150 kg / mol, more preferably 102 kg / mol;

[0024] Preferably, the molecular weight distribution of the polypropylene carbonate (PPC) is 2.2-3, more preferably 2.6.

[0025] Preferably, the melt index of the polypropylene carbonate (PPC) is 0.3-1.5 g / 10 min;

[0026] Preferably, the number average molecular weight of the polybutylene adipate / terephthalate (PBAT) is 60-80 kg / mol, more preferably 67 kg / mol. Preferably, the molecular weight distribution of the PBAT is 2.2-3, more preferably 2.4.

[0027] Preferably, the melt index of the polybutylene adipate / terephthalate (PBAT) is 3-5 g / 10 min;

[0028] Preferably, the number average molecular weight of the polypropylene carbonate diol (PPC diol) is 2000-2800 g / mol, more preferably 2200 g / mol.

[0029] Preferably, the polycarbonate content of the polypropylene carbonate diol (PPC diol) is 40%-48%, more preferably 42%.

[0030] Preferably, the viscosity of the polypropylene carbonate diol (PPC diol) is 2800-3400 Pa·s; more preferably 2890 Pa·s.

[0031] The viscosity test conditions are: 80°C, stirring with rotor #3.

[0032] The present invention also provides a method for preparing the above-mentioned biodegradable film, comprising the following steps:

[0033] The components of the mechanical support layer are mixed, melt-granulated, and then cast to obtain a mechanical support layer film. After cooling, a solution containing polypropylene carbonate diol (PPC diol) is coated on the surface of the mechanical support layer film, and the biodegradable film is obtained by drying and winding.

[0034] Preferably, the temperature of the melt granulation is 140°C-160°C;

[0035] Preferably, the casting temperature is 180°C-200°C.

[0036] Preferably, in the solution containing polypropylene carbonate diol (PPC diol), the mass content of polypropylene carbonate diol (PPC diol) in the solvent is 10 wt % to 30 wt %.

[0037] Preferably, the solvent is selected from ethyl acetate, methanol or butanone.

[0038] Preferably, the cooling temperature is 4°C-15°C; more preferably 8°C-10°C.

[0039] Preferably, the drying temperature is 25°C-45°C; more preferably 30°C-40°C.

[0040] The melt granulation in the above preparation method is preferably carried out using a twin-screw.

[0041] The temperature of the double screw is 140°C-160°C.

[0042] The casting is preferably performed using a casting machine.

[0043] In some specific embodiments of the present invention, the mechanical support layer film cast by a casting machine is cooled by a cold roller.

[0044] After cooling, a solution containing polypropylene carbonate diol (PPC diol) is coated on the surface of the mechanical support layer film, and then the solvent in the solution is volatilized through a drying tunnel, and the film is rolled up to obtain the biodegradable film.

[0045] The processing temperature of the tape casting machine is preferably 180°C-200°C.

[0046] The temperature of the cold roller is preferably 4°C-15°C; more preferably 10°C.

[0047] The temperature of the drying tunnel is preferably 25°C-45°C, more preferably 30°C.

[0048] The time of passing through the drying tunnel is preferably 0.2-1.5 min.

[0049] The present invention also provides the application of the above-mentioned biodegradable film or the biodegradable film prepared by the above-mentioned preparation method in agriculture, garbage collection and treatment, and food packaging.

[0050] Preferably, the viscosity of the biodegradable film is greater than or equal to 2.2±0.1N;

[0051] Preferably, the film thickness error of the biodegradable film is less than 8%.

[0052] Compared to existing technologies, the biodegradable film provided by the present invention comprises a mechanical support layer and a self-adhesive layer connected in sequence. The mechanical support layer comprises the following components, by weight: 5-80 parts polypropylene carbonate; 18.5-94.5 parts PBAT; and 0.5-1.5 parts compatibilizer. The self-adhesive layer is polypropylene carbonate diol. The biodegradable film has a thickness of 10-50 μm. This biodegradable film has uniform thickness, high viscosity, and high transverse and longitudinal tensile strength, making it more suitable for daily use. DETAILED DESCRIPTION

[0053] To further illustrate the present invention, the biodegradable film provided by the present invention, its preparation method and application are described in detail below with reference to the examples.

[0054] The PPC diol is laboratory-produced by adding a dimetallic catalyst (DMC) and a chain transfer agent to a reactor, injecting carbon dioxide at a certain temperature, adding propylene oxide for prepolymerization, and then adding the catalyst for reaction. The specific polymerization process is described in Chinese invention patent CN 116836379 A.

[0055] The compatibilizer is a laboratory-made terpolymer of carbon dioxide, propylene oxide, and a functional monomer, wherein the functional monomer is selected from allyl glycidyl ether or glycidyl methacrylate. It can be prepared according to the document High-Performance Biodegradable PBAT / PPC Composite Film Through Reactive Compatibilizer. Chinese Journal of Polymer Science (2022) 8:411 or the Chinese invention patent "A branched PPC-based film and its preparation method" (authorization number CN113683764B).

[0056] The PBAT and PPC used were purchased from Zhejiang Huafeng Environmental Protection Co., Ltd.; the ethyl acetate, methanol, and butanone used were all analytical grade reagents.

[0057] Example 1

[0058] 0.5 kg of PPC with a number average molecular weight of 102 kg / mol and a molecular weight distribution of 2.6, 9.45 kg of PBAT with a number average molecular weight of 67 kg / mol, a molecular weight distribution of 2.4, and a melt index of 3.8 g / 10 min, and 0.05 kg of a compatibilizer with a number average molecular weight of 34 kg / mol and a molecular weight distribution of 4.1 were placed in a blender and stirred at 50 r / min for 3 minutes. The mixture was taken out and added to a twin-screw extruder. The twin-screw temperatures were set to 140°C in zone 1, 145°C in zone 2, 150°C in zone 3, 155°C in zone 4, 160°C in zone 5, 160°C in zone 6, 160°C in zone 7, 160°C in zone 8, 160°C in zone 9, 160°C in zone 10, 155°C in zone 11, and 155°C in the die head. Granulation was performed to obtain the modified material for the mechanical support layer.

[0059] 1 kg of PPC diol with a number average molecular weight of 2200 g / mol, a polycarbonate content of 42%, and a viscosity of 2890 Pa·s (rotor #3 at 80°C) was placed in a plastic bucket with 9 kg of ethyl acetate and stirred at 30 r / min using a mechanical stirrer for 4 hours to obtain a PPC diol solution.

[0060] The modified material of the mechanical support layer is added to the casting machine, the temperature of the casting machine is set to 180°C in zone 1, 185°C in zone 2, 190°C in zone 3, 200°C in the machine head, and the temperature of the cooling roller is set to 10°C. The cast film is cooled by the cooling roller, coated with PPC diol solution, and then passed through a 30°C drying tunnel for 30 seconds and wound at a speed of 10m / min to obtain a self-adhesive biodegradable film.

[0061] Its thickness is 20 microns. The performance test is shown in Table 1, and the test standard refers to BB / T 0024-2018. The film thickness test is shown in Table 1, and the test standard refers to GB / T 6672.

[0062] Example 2

[0063] 8kg of PPC with a number average molecular weight of 102kg / mol and a molecular weight distribution of 2.6, 1.85kg of PBAT with a number average molecular weight of 67kg / mol, a molecular weight distribution of 2.4, and a melt index of 3.8g / 10min, and 0.15kg of a compatibilizer with a number average molecular weight of 34kg / mol and a molecular weight distribution of 4.1 were placed in a blender and stirred at 50r / min for 3 minutes. The mixture was taken out and added to a twin-screw extruder. The twin-screw temperatures were set to 140°C in zone 1, 145°C in zone 2, 150°C in zone 3, 155°C in zone 4, 160°C in zone 5, 160°C in zone 6, 160°C in zone 7, 160°C in zone 8, 160°C in zone 9, 160°C in zone 10, 155°C in zone 11, and 155°C in the die head. Granulation was performed to obtain the modified material for the mechanical support layer.

[0064] 1 kg of PPC diol having a number average molecular weight of 2200 g / mol, a polycarbonate content of 42%, and a viscosity of 2890 Pa·s (rotor #3 at 80°C) and 9 kg of ethyl acetate were placed in a plastic bucket and stirred at 30 r / min using a mechanical stirrer for 4 hours to obtain a PPC diol solution.

[0065] The modified material of the mechanical support layer is added to the casting machine, the temperature of the casting machine is set to 180°C in zone 1, 185°C in zone 2, 190°C in zone 3, 200°C in the machine head, and the temperature of the cooling roller is set to 10°C. The cast film is cooled by the cooling roller, coated with PPC diol solution, and then passed through a 30°C drying tunnel for 30 seconds and wound at a speed of 10m / min to obtain a self-adhesive biodegradable film.

[0066] Its thickness is 20 microns. The performance test is shown in Table 1, and the test standard refers to BB / T 0024-2018. The film thickness test is shown in Table 1, and the test standard refers to GB / T 6672.

[0067] Example 3

[0068] 0.5 kg of PPC with a number average molecular weight of 102 kg / mol and a molecular weight distribution of 2.6, 9.45 kg of PBAT with a number average molecular weight of 67 kg / mol, a molecular weight distribution of 2.4, and a melt index of 3.8 g / 10 min, and 0.05 kg of a compatibilizer with a number average molecular weight of 34 kg / mol and a molecular weight distribution of 4.1 were placed in a mixer and stirred at 50 r / min for 3 minutes. The mixture was taken out and added to a twin-screw extruder. The twin-screw temperature was set to 140°C in zone 1, 145°C in zone 2, 150°C in zone 3, 155°C in zone 4, 160°C in zone 5, 160°C in zone 6, 160°C in zone 7, 160°C in zone 8, 160°C in zone 9, 160°C in zone 10, 155°C in zone 11, and 155°C in the die head. Granulation was performed to obtain the modified material for the mechanical support layer.

[0069] 3 kg of PPC diol with a number average molecular weight of 2200 g / mol, a polycarbonate content of 42%, and a viscosity of 2890 Pa·s (rotor #3 at 80°C) and 7 kg of ethyl acetate were placed in a plastic bucket and stirred at 30 r / min using a mechanical stirrer for 4 hours to obtain a PPC diol solution.

[0070] The modified material of the mechanical support layer is added to the casting machine, the temperature of the casting machine is set to 180°C in zone 1, 185°C in zone 2, 190°C in zone 3, 200°C in the machine head, and the temperature of the cooling roller is set to 10°C. The cast film is cooled by the cooling roller, coated with PPC diol solution, and then passed through a 30°C drying tunnel for 30 seconds and wound at a speed of 10m / min to obtain a self-adhesive biodegradable film.

[0071] Its thickness is 20 microns. The performance test is shown in Table 1, and the test standard refers to BB / T 0024-2018. The film thickness test is shown in Table 1, and the test standard refers to GB / T 6672.

[0072] Example 4

[0073] 8kg of PPC with a number average molecular weight of 102kg / mol and a molecular weight distribution of 2.6, 1.85kg of PBAT with a number average molecular weight of 67kg / mol, a molecular weight distribution of 2.4, and a melt index of 3.8g / 10min, and 0.15kg of a compatibilizer with a number average molecular weight of 34kg / mol and a molecular weight distribution of 4.1 were placed in a blender and stirred at 50r / min for 3 minutes. The mixture was taken out and added to a twin-screw extruder. The twin-screw temperatures were set to 140°C in zone 1, 145°C in zone 2, 150°C in zone 3, 155°C in zone 4, 160°C in zone 5, 160°C in zone 6, 160°C in zone 7, 160°C in zone 8, 160°C in zone 9, 160°C in zone 10, 155°C in zone 11, and 155°C in the die head. Granulation was performed to obtain the modified material for the mechanical support layer.

[0074] 1 kg of PPC diol with a number average molecular weight of 2200 g / mol, a polycarbonate content of 42%, and a viscosity of 2890 Pa·s (rotor #3 at 80°C) and 9 kg of butanone were placed in a plastic barrel and stirred at 30 r / min with a mechanical stirrer for 4 hours to obtain a PPC diol solution.

[0075] The modified material of the mechanical support layer is added to the casting machine, the temperature of the casting machine is set to 180°C in zone 1, 185°C in zone 2, 190°C in zone 3, 200°C in the machine head, and the temperature of the cooling roller is set to 10°C. The cast film is cooled by the cooling roller, coated with PPC diol solution, and then passed through a 30°C drying tunnel for 30 seconds and wound at a speed of 10m / min to obtain a self-adhesive biodegradable film.

[0076] Its thickness is 20 microns. The performance test is shown in Table 1, and the test standard refers to BB / T 0024-2018. The film thickness test is shown in Table 1, and the test standard refers to GB / T 6672.

[0077] Example 5

[0078] 8kg of PPC with a number average molecular weight of 102kg / mol and a molecular weight distribution of 2.6, 1.85kg of PBAT with a number average molecular weight of 67kg / mol, a molecular weight distribution of 2.4, and a melt index of 3.8g / 10min, and 0.15kg of a compatibilizer with a number average molecular weight of 34kg / mol and a molecular weight distribution of 4.1 were placed in a blender and stirred at 50r / min for 3 minutes. The mixture was taken out and added to a twin-screw extruder. The twin-screw temperatures were set to 140°C in zone 1, 145°C in zone 2, 150°C in zone 3, 155°C in zone 4, 160°C in zone 5, 160°C in zone 6, 160°C in zone 7, 160°C in zone 8, 160°C in zone 9, 160°C in zone 10, 155°C in zone 11, and 155°C in the die head. Granulation was performed to obtain the modified material for the mechanical support layer.

[0079] 1 kg of PPC diol with a number average molecular weight of 2200 g / mol, a polycarbonate content of 42%, and a viscosity of 2890 Pa·s (rotor #3 at 80°C) was placed in a plastic bucket with 9 kg of ethyl acetate and stirred at 30 r / min using a mechanical stirrer for 4 hours to obtain a PPC diol solution.

[0080] The modified material of the mechanical support layer is added to the casting machine, the temperature of the casting machine is set to 180°C in zone 1, 185°C in zone 2, 190°C in zone 3, 200°C in the machine head, and the temperature of the cooling roller is set to 10°C. The cast film is cooled by the cooling roller, coated with PPC diol solution, and then passed through a 30°C drying tunnel for 30 seconds and wound at a speed of 10m / min to obtain a self-adhesive biodegradable film.

[0081] Its thickness is 50 microns. The performance test is shown in Table 1, and the test standard refers to BB / T 0024-2018. The film thickness test is shown in Table 1, and the test standard refers to GB / T 6672.

[0082] The thickness of the biodegradable film prepared in Example 5 is different from that in Example 2, which is increased from 20 μm in Example 2 to 50 μm.

[0083] Comparative Example 1

[0084] 0.5 kg of PPC with a number average molecular weight of 102 kg / mol and a molecular weight distribution of 2.6 and 9.5 kg of PBAT with a number average molecular weight of 67 kg / mol, a molecular weight distribution of 2.4, and a melt index of 3.8 g / 10 min were placed in a blender and stirred at 50 r / min for 3 minutes. The mixture was taken out and added to a twin-screw extruder. The twin-screw temperatures were set to 140°C in zone 1, 145°C in zone 2, 150°C in zone 3, 155°C in zone 4, 160°C in zone 5, 160°C in zone 6, 160°C in zone 7, 160°C in zone 8, 160°C in zone 9, 160°C in zone 10, 155°C in zone 11, and 155°C in the die head. Granulation was performed to obtain the modified material for the mechanical support layer.

[0085] 1 kg of PPC diol with a number average molecular weight of 2200 g / mol, a polycarbonate content of 42%, and a viscosity of 2890 Pa Pa·s (rotor #3 at 80°C) and 9 kg of ethyl acetate were placed in a plastic bucket and stirred at 30 r / min with a mechanical stirrer for 4 hours to obtain a PPC diol solution.

[0086] The modified material of the mechanical support layer is added to the casting machine, the temperature of the casting machine is set to 180°C in zone 1, 185°C in zone 2, 190°C in zone 3, 200°C in the machine head, and the temperature of the cooling roller is set to 10°C. The cast film is cooled by the cooling roller, coated with PPC diol solution, and then passed through a 30°C drying tunnel for 30 seconds and wound at a speed of 10m / min to obtain a self-adhesive biodegradable film.

[0087] Its thickness is 20 microns. The performance test is shown in Table 1, and the test standard refers to BB / T 0024-2018. The film thickness test is shown in Table 1, and the test standard refers to GB / T 6672.

[0088] Compared with Example 1, Comparative Example 1 added less compatibilizer, and the rest was the same.

[0089] Comparative Example 2

[0090] 8kg of PPC with a number average molecular weight of 102kg / mol and a molecular weight distribution of 2.6, 1.85kg of PBAT with a number average molecular weight of 67kg / mol, a molecular weight distribution of 2.4, and a melt index of 3.8g / 10min, and 0.15kg of a compatibilizer with a number average molecular weight of 34kg / mol and a molecular weight distribution of 4.1 were placed in a blender and stirred at 50r / min for 3 minutes. The mixture was taken out and added to a twin-screw extruder. The twin-screw temperatures were set to 140°C in zone 1, 145°C in zone 2, 150°C in zone 3, 155°C in zone 4, 160°C in zone 5, 160°C in zone 6, 160°C in zone 7, 160°C in zone 8, 160°C in zone 9, 160°C in zone 10, 155°C in zone 11, and 155°C in the die head. Granulation was performed to obtain the modified material for the mechanical support layer.

[0091] 1 kg of PPC diol with a number average molecular weight of 2200 g / mol, a polycarbonate content of 42%, and a viscosity of 2890 Pa Pa·s (rotor #3 at 80°C) and 9 kg of dichloromethane were placed in a plastic barrel and stirred at 30 r / min with a mechanical stirrer for 4 hours to obtain a PPC diol solution.

[0092] The modified material of the mechanical support layer is added to the casting machine. The temperature of the casting machine is set to 180°C in zone 1, 185°C in zone 2, 190°C in zone 3, 200°C in the machine head, and the temperature of the cooling roller is set to 10°C. The cast film is cooled by the cooling roller, coated with PPC diol solution, and then passed through a 30°C drying tunnel for 30 seconds and wound at a speed of 10m / min.

[0093] Comparative Example 2 differed from Example 2 in the solvent used in the preparation of PPC diol, with dichloromethane replacing ethyl acetate. The remaining solvents remained unchanged. Due to the high solubility of dichloromethane for PPC and PBAT, the prepared membrane exhibited shrinkage and wrinkles, and a complete membrane could not be obtained.

[0094] Comparative Example 3

[0095] 8kg of PPC with a number average molecular weight of 102kg / mol and a molecular weight distribution of 2.6, 1.85kg of PBAT with a number average molecular weight of 67kg / mol, a molecular weight distribution of 2.4, and a melt index of 3.8g / 10min, and 0.15kg of a compatibilizer with a number average molecular weight of 34kg / mol and a molecular weight distribution of 4.1 were placed in a blender and stirred at 50r / min for 3 minutes. The mixture was taken out and added to a twin-screw extruder. The twin-screw temperatures were set to 140°C in zone 1, 145°C in zone 2, 150°C in zone 3, 155°C in zone 4, 160°C in zone 5, 160°C in zone 6, 160°C in zone 7, 160°C in zone 8, 160°C in zone 9, 160°C in zone 10, 155°C in zone 11, and 155°C in the die head. Granulation was performed to obtain the modified material for the mechanical support layer.

[0096] 4 kg of PPC diol having a number average molecular weight of 2200 g / mol, a polycarbonate content of 42%, and a viscosity of 2890 Pa Pa·s (rotor #3 at 80°C) and 6 kg of ethyl acetate were placed in a plastic bucket and stirred at 30 r / min using a mechanical stirrer for 4 hours to obtain a PPC diol solution.

[0097] The modified material of the mechanical support layer is added to the casting machine. The temperature of the casting machine is set to 180°C in zone 1, 185°C in zone 2, 190°C in zone 3, 200°C in the machine head, and the temperature of the cooling roller is set to 10°C. The cast film is cooled by the cooling roller, coated with PPC diol solution, and then passed through a 30°C drying tunnel for 30 seconds and wound at a speed of 10m / min.

[0098] Comparative Example 3 differs from Example 2 in that the PPC diol concentration used in preparation was changed from 10% to 40%, with all other parameters remaining unchanged. This increased concentration resulted in poor dissolution of the PPC diol, resulting in uneven coating. Protrusions appeared on the surface of the prepared film, failing to address the uneven film product.

[0099] Table 1 shows the performance test results of the biodegradable films prepared in Examples 1-5 and Comparative Example 1.

[0100] Table 1 Test data of biodegradable films prepared in Example

[0101]

[0102] The results in Table 1 demonstrate that the biodegradable film produced using the PPC diol solution coating process exhibits excellent uniformity and minimal thickness variation, with the thickness variation for a 20-micron film within 1.6 microns. Comparative Example 1 demonstrates that the compatibilizer primarily enhances the compatibility of PPC and PBAT. The mechanical properties of the biodegradable film without the compatibilizer, including both tensile strength and elongation at break, are significantly reduced.

[0103] The above embodiments are only intended to help understand the method and core concept of the present invention. It should be noted that those skilled in the art can make various improvements and modifications to the present invention without departing from the principles of the present invention, and such improvements and modifications also fall within the scope of protection of the claims of the present invention.

Claims

1. A biodegradable film, characterized in that: It includes a mechanical support layer and a self-adhesive layer connected in sequence; The mechanical support layer comprises the following components by weight: Polypropylene carbonate: 5-80 parts; Polybutylene adipate / terephthalate: 18.5-94.5 parts; Compatibilizer: 0.5-1.5 parts; The self-adhesive layer is polypropylene carbonate glycol; The biodegradable film has a thickness of 10-50 μm.

2. The biodegradable film according to claim 1, characterized in that: The compatibilizer is selected from a terpolymer of carbon dioxide, propylene oxide and a functional monomer, wherein the functional monomer is selected from allyl glycidyl ether or glycidyl methacrylate.

3. The biodegradable film according to claim 1, characterized in that: The polypropylene carbonate has a number average molecular weight of 100-150 kg / mol, a molecular weight distribution of 2.2-3, and a melt index of 0.3-1.5 g / 10 min; The PBAT has a number average molecular weight of 60-80 kg / mol, a molecular weight distribution of 2.2-3, and a melt index of 3-5 g / 10 min; The number average molecular weight of the polypropylene carbonate diol is 2000-2800 g / mol, the polycarbonate content is 40%-48%, and the viscosity is 2800-3400 Pa·s.

4. The method for preparing the biodegradable film according to any one of claims 1 to 3, characterized in that: The following steps are involved: The components of the mechanical support layer of claim 1 are mixed, melt-granulated, and then cast to obtain a mechanical support layer film. After cooling, a solution containing polypropylene carbonate diol is coated on the surface of the mechanical support layer film, and the biodegradable film is obtained by drying and rolling.

5. The preparation method according to claim 4, characterized in that: The temperature of the melt granulation is 140°C-160°C; The casting temperature is 180°C-200°C.

6. The preparation method according to claim 4, characterized in that: In the solution containing polypropylene carbonate diol, the mass content of polypropylene carbonate diol in the solvent is 10wt%-30wt%.

7. The preparation method according to claim 4, characterized in that: The solvent is selected from ethyl acetate, methanol or butanone.

8. The preparation method according to claim 4, characterized in that: The cooling temperature is 4°C-15°C; The drying temperature is 25°C-45°C.

9. Use of the biodegradable film according to any one of claims 1 to 3 or the biodegradable film prepared by the preparation method according to any one of claims 4 to 8 in agriculture, garbage collection and treatment, and food packaging.

10. The use according to claim 9, characterized in that: The viscosity of the biodegradable film is greater than or equal to 2.2±0.1N; The film thickness error of the biodegradable film is less than 8%.

Citation Information

Patent Citations

  • A branched PPC base film and its preparation method

    CN113683764B

  • Green industrial production method and application of high-purity polycarbonate-ether polyol

    CN116836379A

  • Biodegradable wrapping film as well as preparation method and application thereof

    CN117165051A

  • Biodegradable wrapping film as well as preparation method and application thereof

    CN117210159A

  • Method for manufacturing functional film

    JP2011194728A